2014
DOI: 10.1523/jneurosci.3413-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Enhancing Treatment with a PPARγ Agonist Normalizes Dentate Granule Cell Presynaptic Function in Tg2576 APP Mice

Abstract: Hippocampal network hyperexcitability is considered an early indicator of Alzheimer's disease (AD) memory impairment. Some AD mouse models exhibit similar network phenotypes. In this study we focused on dentate gyrus (DG) granule cell spontaneous and evoked properties in 9-month-old Tg2576 mice that model AD amyloidosis and cognitive deficits. Using whole-cell patch-clamp recordings, we found that Tg2576 DG granule cells exhibited spontaneous EPSCs that were higher in frequency but not amplitude compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 68 publications
4
46
0
Order By: Relevance
“…MG accumulates under conditions of hyperglycemia, impaired glucose metabolism or oxidative stress (Nenov et al, 2014). In this study, we demonstrated that DMY protected PC12 cells from MGinduced oxidative and glucose metabolic disorders.…”
Section: Discussionsupporting
confidence: 52%
“…MG accumulates under conditions of hyperglycemia, impaired glucose metabolism or oxidative stress (Nenov et al, 2014). In this study, we demonstrated that DMY protected PC12 cells from MGinduced oxidative and glucose metabolic disorders.…”
Section: Discussionsupporting
confidence: 52%
“…Previously we showed that RSG diet ameliorates aberrant synaptic transmission and neuronal excitability in Tg2576 DG granule cells (Nenov et al, 2014, 2015). Treatment with RSG significantly restores repetitive firing in two types (type 1 and type 2) of electrophysiologically characterized DG granule cells via bi-directional modulation of spike after-depolarization (Nenov et al, 2014, 2015).…”
Section: Resultsmentioning
confidence: 94%
“…Treatment with RSG significantly restores repetitive firing in two types (type 1 and type 2) of electrophysiologically characterized DG granule cells via bi-directional modulation of spike after-depolarization (Nenov et al, 2014, 2015). Here, in order to characterize functional outcomes associated with changes in Tg2576 AIS expression profiles for PanNav channels, FGF14 and another AIS marker, Ankyrin-G, we assessed time to rise and time to decay half-amplitude of action potentials in two previously identified types of DG granule cells (Nenov et al, 2015; Tempia et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations